Ectomycorrhizal Fungi of Salix Rotundifolia Trautv. II. Impact of Surface Applied Prudhoe Bay Crude Oil on Mycorrhizal Root Respiration and Cold Acclimation - Linkins, A.E.; Antibus, R.K. (ARCTIC, 1978)
Ectomycorrhizal root tips of Salix rotundifolia Trautv. removed from Barrow, Alaska tundra treated with 5 or 12 l/m² Prudhoe Bay crude oil on 1 July 1975 showed decreased respiration rates within 48 hr after surface application of oil. Oil treated roots continued to have depressed respiration rates throughout the summer. The following summer, respiration rates of the 5 l/m² oil treated roots were higher than controls. With respiration of the 12 l/m² treated roots only 20% below controls. However, during the summer, respiration rates declined very rapidly, probably due to water stress caused by drought conditions. The third summer, respiration rates of all root samples were quite similar, with all rates low, probably due to continued water stress. Viable root biomass declined from year to year in the oiled soils. Analysis of cold acclimation by Arrhenius plots of respiration rates shows losses in cold acclimation after oil treatment. Ectomycorrhizal roots of S. rotundifolia from the oil impregnated soils of a natural oil seep at Cape Simpson, Alaska showed a minimum loss in respiration rates and cold acclimation after exposure to fresh crude oil.